METHODOLOGICAL FEATURES OF EDUCATION OF CHILDREN OF JUNIOR SCHOOL AGE (Academia Science Repository, 2023)
The patriotic education of the younger generation has always been one of the most important tasks of the school. This is a complex pedagogical process, which is based on the formation of patriotism as a personal quality. . Theoretical ideas are explained on the basis of examples.